Genistein: A Review on its Anti-Inflammatory Properties - Goh, Yu Xian; Jalil, Juriyati; Lam, Kok Wai; Husain, Khairana; Premakumar, Chandini Menon (Frontiers in Pharmacology, 2022)
Nowadays, non-resolving inflammation is becoming a major trigger in various diseases as it plays a significant role in the pathogenesis of atherosclerosis, asthma, cancer, obesity, inflammatory bowel disease, chronic obstructive pulmonary disease, neurodegenerative disease, multiple sclerosis, and rheumatoid arthritis. However, prolonged use of anti-inflammatory drugs is usually accompanied with undesirable effects and hence more patients tend to seek for natural compounds as alternative medicine. Considering the fact above, there is an urgency to discover and develop potential novel, safe and efficacious natural compounds as drug candidates for future anti-inflammatory therapy. Genistein belongs to the flavonoid family, in the subgroup of isoflavones. It is a phytoestrogen that is mainly derived from legumes. It is a naturally occurring chemical constituent with a similar chemical structure to mammalian estrogens. It is claimed to exert many beneficial effects on health, such as protection against osteoporosis, reduction in the risk of cardiovascular disease, alleviation of postmenopausal symptoms and anticancer properties. In the past, numerous in vitro and in vivo studies have been conducted to investigate the anti-inflammatory potential of genistein. Henceforth, this review aims to summarize the anti-inflammatory properties of genistein linking with the signaling pathways and mediators that are involved in the inflammatory response as well as its toxicity profile. The current outcomes are analysed to highlight the prospect as a lead compound for drug discovery. Data was collected using PubMed, ScienceDirect, SpringerLink and Scopus databases. Results showed that genistein possessed strong anti-inflammatory activities through inhibition of various signaling pathways such as nuclear factor kappa-B (NF-κB), prostaglandins (PGs), inducible nitric oxide synthase (iNOS), proinflammatory cytokines and reactive oxygen species (ROS). A comprehensive assessment of the mechanism of action in anti-inflammatory effects of genistein is included. However, evidence for the pharmacological effects is still lacking. Further studies using various animal models to assess pharmacological effects such as toxicity, pharmacokinetics, pharmacodynamics, and bioavailability studies are required before clinical studies can be conducted. This review will highlight the potential use of genistein as a lead compound for future drug development as an anti-inflammatory agent.